Let us be free from “academentia” - Favaro, Laura (Cuestiones de Género: de la igualdad y la diferencia, 2024)
“Survivor of academentia” is how one former lecturer in sociology described herself when I interviewed her for my ethnography of academia. In particular, the research was exploring the “gender wars”, namely the disputes around sex and gender that have escalated dramatically since the mid-2010s in Britain and increasingly also in many other countries. This article builds on feminist and other critical uses of the term academentia with original insights from interview and document data about the detrimental impact of queer theory and politics. The hope is to stimulate further inquiry into the push towards queering at universities, and beyond, as well as into the connections between the transgender and mad movements.